Studying the chromatographic separation of caffeine, theophylline, and theobromine - Hassan, Hassanain A.; Salih, Miqat Hasan; Alhassani, Maha H. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Theobromine, theophylline, and caffeine retention times in a C18 HPLC column (stationary phase) were investigated as a function of mobile phase flow rate, mobile phase composition, and column temperature. When the mobile phase flow rate increased from 0.1 to 1 mL/min and the methanol concentration increased from 5 to 30%, the retention time and peak width of these three compounds were found to be reduced. While there was a small influence of increasing the mobile phase flow rate on the resolution, decreasing the methanol concentration in the mobile phase considerably reduced the resolution. In addition, the mobile phase flow rate and composition were determined to have a more significant impact than the column temperature. According to the findings, theobromine, theophylline, and caffeine were most effectively separated by liquid chromatography at a flow rate of 0.5 mL/min with a mobile phase methanol concentration of 15%.